Nasionalism: Character Education Orientation in Learning Development - Dian Arief Pradana; Mahfud Mahfud; Candra Hermawan; Herdiana Dyah Susanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The values of nationalism can be learned from educational materials that are oriented towards character development. Character education is part of a revolutionary zone among students, therefore character education is a very important part to be urgently developed in the minds of the student head because students are the next generation who will lead the nation and state. Character learning that is oriented towards the values of nationalism can overcome various social problems. Building character for the current generation is one of the goals of national education. The Ministry of National Education (2011) describes the matter of character building through educational institutions that in the implementation process designing students to have caring care and responsibility. This analysis concerns that character education is part of the formation of identity, selfconcept, self-esteem, psychology, personality, character, individualistic behavior, character and character. This writing method uses a descriptive method. Discussion: 1). Zone of Nationalism and Learning. 2). Character Education and Learning Development. Conclusion: Character learning in universities is one of the development of learning which should provide an effective space in internalizing the values of Nationalism in shaping the character and civilization of the Indonesian nation to students